Waterproof housing building exterior wall coating and preparation method thereof
The nanosilicon oxide was formed by the reaction of glucose, sodium silicate and cerium nitrate in waterproof coatings, and combined with zinc acetate and isophorone diisocyanate treatment to form zinc oxide and modified aluminum powder, solving the leakage of the building The leakage problem has achieved high-performance waterproofing and corrosion resistance, and improved the protection effect of building exterior walls.
Patent Information
- Application Number
- CN202411232614.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Leakage in buildings is common, and existing waterproof coatings are difficult to meet the needs of modern buildings for high-performance waterproof, anti-seepage, weather resistance and water resistance.
A preparation method for waterproof room building exterior wall coating is adopted to produce nano-silicon oxides by reacting aqueous solutions of glucose, sodium silicate and cerium nitrate, combined with a composite aqueous solution of zinc acetate, ethylene glycol and isophorone diisocyanate to form Zinc oxide and modified aluminum powder are finally mixed with components such as polyether polyol and defoaming agent to form a high-performance waterproof film.
The prepared paint film has good waterproofing and corrosion resistance, which significantly improves the protection effect of building exterior walls and reduces maintenance costs.
Smart Images

Figure BDA0005026689130000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waterproof coatings, and in particular to a waterproof building exterior wall coating and a preparation method thereof. Background Art
[0002] Leakage in buildings is common in all fields. Building waterproofing has become a high-profile issue in construction projects, especially in modern buildings, where the demand for coating performance is higher in complex and special fields. Waterproof coating refers to a coating that can form a waterproof film with certain elongation, elasticity, plasticity, crack resistance, impermeability, weather resistance, and water resistance after curing, and plays a role in waterproofing, anti-seepage and protection. Summary of the invention
[0003] To this end, the present invention provides a method for preparing a waterproof exterior wall coating for housing construction, the preparation steps comprising:
[0004] (1) preparing an aqueous solution of glucose, an aqueous solution of sodium silicate, and an aqueous solution of cerium nitrate in a reaction kettle; stirring the aqueous solution of glucose, and then adding the aqueous solution of sodium silicate to the aqueous solution of glucose under stirring, stirring for more than 20 minutes after the addition is completed, and then adding the aqueous solution of cerium nitrate, and adding ammonia water dropwise to adjust the pH value of the solution to 8; after the addition is completed, sealing the reaction kettle, heating to 180±5° C. and keeping the temperature for more than 20 hours, air cooling to room temperature after keeping the temperature, opening the reaction kettle, separating the solid and the liquid, washing the solid phase with deionized water for more than 3 times, drying at 80° C. for more than 3 hours, and then calcining at 600° C. for more than 5 hours to obtain a powder solid phase;
[0005] (2) preparing a composite aqueous solution of zinc acetate and ethylene glycol, immersing the powder solid phase in the composite aqueous solution of zinc acetate and ethylene glycol, stirring for more than 5 minutes, then separating the solid and the liquid, calcining the solid phase at 400° C. for 30 to 40 minutes, air cooling to room temperature, and then immersing again in the composite aqueous solution of zinc acetate and ethylene glycol, stirring for more than 5 minutes, separating the solid and the liquid, and calcining the solid phase at 400° C. for 30 to 40 minutes; the above immersing, stirring, solid-liquid separation, calcining, and air cooling steps are a whole set, and are repeated for more than 6 sets in total, forming zinc oxide on the surface of the powder to obtain a primary treated powder;
[0006] (3) preparing a dimethyl sulfoxide solution of isophorone diisocyanate; adding the once treated powder to dimethyl sulfoxide and stirring for more than 10 minutes to form a dispersion, heating the dispersion to 70±3° C. in a water bath and keeping it warm, then adding the dimethyl sulfoxide solution of isophorone diisocyanate and dibutyltin dilaurate to the dispersion under stirring, and continuing to stir at a constant temperature of 70±3° C. for more than 6 hours after the addition is completed, and then air cooling to room temperature, solid-liquid separation, washing the solid phase with dimethyl sulfoxide for more than two times, and then washing with deionized water for more than three times, and drying at 80° C. for more than 3 hours to obtain a powder additive;
[0007] (4) passing aluminum powder through a 1000 mesh sieve, soaking the sieved powder in acetone for ultrasonic cleaning for more than 10 minutes, and then separating the solid and liquid, drying the solid phase at 60° C. for 15 to 20 minutes, adding the dried aluminum powder to anhydrous ethanol, heating to 70±3° C. in a water bath in a nitrogen atmosphere, and then adding 3-aminopropyltriethoxysilane under stirring. After the addition is completed, stirring at a constant temperature of 70±3° C. in a nitrogen protective atmosphere for more than 3 hours, separating the solid and liquid after insulation, and drying the solid phase at 60° C. for more than 2 hours to obtain modified aluminum powder;
[0008] (5) Add the dehydrated polyether polyol to the reaction kettle, heat it to 80±2° C. in a water bath, and then add toluene diisocyanate. After the addition is completed, continue to stir at a constant temperature of 80±2° C. for 2 to 3 hours to obtain component A; mix 4,4'-diamino-3,3'-dichlorodiphenylmethane, the powder additive, the modified aluminum powder, titanium dioxide powder, calcium carbonate, defoaming agent, and dibutyl phthalate to obtain component B; mix component A and component B to obtain the waterproof building exterior wall coating.
[0009] Furthermore, in the step (1), in the aqueous solution of glucose, the concentration of glucose is 15-16 g / L, and the solvent is water; in the aqueous solution of sodium silicate, the mass percentage of sodium silicate is 4%-5%, and the solvent is water; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 10-20 g / L, and the solvent is water; the volume ratio of adding the aqueous solution of sodium silicate and the aqueous solution of cerium nitrate to the aqueous solution of glucose is glucose aqueous solution: sodium silicate aqueous solution: cerium nitrate aqueous solution = 100:2-3:0.8-1; the mass percentage of the solute in the ammonia water is 25%.
[0010] Furthermore, in the step (2), in the composite aqueous solution of zinc acetate and ethylene glycol, the concentration of zinc acetate is 30-40 g / L, the concentration of ethylene glycol is 6-9 mL / L, and the solvent is water; the mass ratio of the powder solid phase immersed in the composite aqueous solution of zinc acetate and ethylene glycol is powder solid phase: composite aqueous solution of zinc acetate and ethylene glycol = 1:200.
[0011] Furthermore, in the step (3), the concentration of isophorone diisocyanate in the dimethyl sulfoxide solution of isophorone diisocyanate is 6-8 g / 100 mL, and the solvent is dimethyl sulfoxide; the mass ratio of the once-treated powder added to dimethyl sulfoxide is once-treated powder: dimethyl sulfoxide = 1:80; the mass ratio of the dimethyl sulfoxide solution of isophorone diisocyanate and dibutyltin dilaurate added to the dispersion is dispersion: dimethyl sulfoxide solution of isophorone diisocyanate: dibutyltin dilaurate = 10:5-6:0.2-0.4.
[0012] Furthermore, in the step (4), the dried aluminum powder is added with anhydrous ethanol and 3-aminopropyltriethoxysilane in a ratio of aluminum powder: anhydrous ethanol: 3-aminopropyltriethoxysilane = 10 g: 100 mL: 20-25 mL.
[0013] Furthermore, in the step (5), the components are calculated by weight as follows: 100 parts of polyether polyol, 20-30 parts of toluene diisocyanate, 6-8 parts of 4,4'-diamino-3,3'-dichlorodiphenylmethane, 5-10 parts of the powder additive, 5-10 parts of the modified aluminum powder, 2-6 parts of titanium dioxide powder, 15-18 parts of calcium carbonate, 2-3 parts of defoaming agent, and 2-4 parts of dibutyl phthalate.
[0014] Furthermore, the defoamer is BYK055 defoamer.
[0015] The beneficial effects of the present invention are: the paint film prepared by the method of the present invention has good waterproof effect and corrosion resistance, can play a good protective role on the exterior wall of the building, improve the quality of the exterior wall, and reduce maintenance costs. DETAILED DESCRIPTION
[0016] The present invention will be further described below in conjunction with the embodiments.
[0017] Example 1
[0018] A method for preparing a waterproof exterior wall coating for a building, the preparation steps comprising:
[0019] (1) In a reaction kettle, a glucose aqueous solution is prepared, wherein the glucose concentration in the glucose aqueous solution is 15 g / L, and the solvent is water; an sodium silicate aqueous solution is prepared, wherein the mass percentage of sodium silicate in the sodium silicate aqueous solution is 4%, and the solvent is water; an cerium nitrate aqueous solution is prepared, wherein the cerium nitrate concentration in the cerium nitrate aqueous solution is 10 g / L, and the solvent is water; the glucose aqueous solution is stirred, and then the sodium silicate aqueous solution is added to the glucose aqueous solution under stirring, and after the addition is completed, the sodium silicate aqueous solution is stirred for 20 minutes, and then the cerium nitrate aqueous solution is added. , adding the aqueous solution of sodium silicate and the aqueous solution of cerium nitrate to the aqueous solution of glucose in a volume ratio of the aqueous solution of glucose: the aqueous solution of sodium silicate: the aqueous solution of cerium nitrate = 100:2:0.8; dropping ammonia water to adjust the pH value of the solution to 8, wherein the mass percentage of the solute in the ammonia water is 25%; after the addition is completed, the reactor is sealed, heated to 180±5°C and kept warm for 20 hours, air-cooled to room temperature after keeping warm, the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed with deionized water for 3 times, dried at 80°C for 3 hours, and then calcined at 600°C for 5 hours to obtain a powder solid phase;
[0020] (2) preparing a composite aqueous solution of zinc acetate and ethylene glycol, wherein the concentration of zinc acetate is 30 g / L, the concentration of ethylene glycol is 6 mL / L, and the solvent is water; immersing the powder solid phase in the composite aqueous solution of zinc acetate and ethylene glycol, wherein the mass ratio of the powder solid phase immersed in the composite aqueous solution of zinc acetate and ethylene glycol is powder solid phase: composite aqueous solution of zinc acetate and ethylene glycol = 1:200; stirring for 5 min, then solid-liquid separation, calcining the solid phase at 400° C. for 30 min, air cooling to room temperature, and then immersing again in the composite aqueous solution of zinc acetate and ethylene glycol, stirring for 5 min, solid-liquid separation, and calcining the solid phase at 400° C. for 30 min; the above immersion, stirring, solid-liquid separation, calcining, and air cooling steps are a group as a whole, and a total of 6 groups are repeated to form zinc oxide on the surface of the powder to obtain a primary treated powder;
[0021] (3) preparing a dimethyl sulfoxide solution of isophorone diisocyanate; in the dimethyl sulfoxide solution of isophorone diisocyanate, the concentration of isophorone diisocyanate is 6 g / 100 mL, and the solvent is dimethyl sulfoxide; adding the once treated powder to the dimethyl sulfoxide and stirring for 10 min to form a dispersion, the mass ratio of the once treated powder to the dimethyl sulfoxide is once treated powder: dimethyl sulfoxide = 1:80; heating the dispersion to 70±3° C. in a water bath and then adding the isophorone diisocyanate to the dispersion under stirring; dimethyl sulfoxide solution of isophorone diisocyanate and dibutyltin dilaurate, and adding the dimethyl sulfoxide solution of isophorone diisocyanate and dibutyltin dilaurate to the dispersion in a mass ratio of dispersion: dimethyl sulfoxide solution of isophorone diisocyanate: dibutyltin dilaurate = 10:5:0.2; after the addition is completed, continue to stir at a constant temperature of 70±3°C for 6h, then air cool to room temperature, separate the solid and liquid, wash the solid phase with dimethyl sulfoxide twice, then wash with deionized water 3 times, and dry at 80°C for 3h to obtain a powder additive;
[0022] (4) The aluminum powder is passed through a 1000 mesh sieve, and the sieved powder is immersed in acetone for ultrasonic cleaning for 10 minutes to remove oil, and then the solid-liquid separation is performed, and the solid phase is dried at 60° C. for 15 minutes. The dried aluminum powder is added to anhydrous ethanol, and heated to 70±3° C. in a water bath in a nitrogen atmosphere for insulation, and then 3-aminopropyltriethoxysilane is added under stirring. The dried aluminum powder is added with anhydrous ethanol and 3-aminopropyltriethoxysilane in a ratio of aluminum powder: anhydrous ethanol: 3-aminopropyltriethoxysilane = 10 g: 100 mL: 20 mL; after the addition is completed, the mixture is stirred at a constant temperature of 70±3° C. for 3 hours in a nitrogen protective atmosphere, and the solid-liquid separation is performed after insulation, and the solid phase is dried at 60° C. for 2 hours to obtain modified aluminum powder;
[0023] (5) Weigh the raw material components, and the weight of each component is as follows: 100 parts of dehydrated polyether polyol (330N), 20 parts of toluene diisocyanate, 6 parts of 4,4'-diamino-3,3'-dichlorodiphenylmethane, 5 parts of the powder additive, 5 parts of the modified aluminum powder, 2 parts of titanium dioxide powder, 15 parts of calcium carbonate, 2 parts of BYK055 defoamer, and 2 parts of dibutyl phthalate; add the dehydrated polyether polyol to a reaction kettle, heat it to 80±2°C in a water bath, and then add toluene diisocyanate. After the addition is completed, continue to stir at a constant temperature of 80±2°C for 2 hours to obtain component A; mix 4,4'-diamino-3,3'-dichlorodiphenylmethane, the powder additive, the modified aluminum powder, titanium dioxide powder, calcium carbonate, defoamer, and dibutyl phthalate to obtain component B; mix component A and component B to obtain the waterproof exterior wall coating.
[0024] Example 2
[0025] A method for preparing a waterproof exterior wall coating for a building, the preparation steps comprising:
[0026] (1) In a reaction kettle, a glucose aqueous solution is prepared, wherein the glucose concentration in the glucose aqueous solution is 15 g / L, and the solvent is water; an sodium silicate aqueous solution is prepared, wherein the mass percentage of sodium silicate in the sodium silicate aqueous solution is 4%, and the solvent is water; an cerium nitrate aqueous solution is prepared, wherein the cerium nitrate concentration in the cerium nitrate aqueous solution is 14 g / L, and the solvent is water; the glucose aqueous solution is stirred, and then the sodium silicate aqueous solution is added to the glucose aqueous solution under stirring, and after the addition is completed, the sodium silicate aqueous solution is stirred for 20 minutes, and then the cerium nitrate aqueous solution is added. , adding the aqueous solution of sodium silicate and the aqueous solution of cerium nitrate to the aqueous solution of glucose in a volume ratio of the aqueous solution of glucose: the aqueous solution of sodium silicate: the aqueous solution of cerium nitrate = 100:2:0.9; dropping ammonia water to adjust the pH value of the solution to 8, wherein the mass percentage of the solute in the ammonia water is 25%; after the addition is completed, the reactor is sealed, heated to 180±5°C and kept warm for 20 hours, air-cooled to room temperature after keeping warm, the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed with deionized water for 3 times, dried at 80°C for 3 hours, and then calcined at 600°C for 5 hours to obtain a powder solid phase;
[0027] (2) preparing a composite aqueous solution of zinc acetate and ethylene glycol, wherein the concentration of zinc acetate is 35 g / L, the concentration of ethylene glycol is 7 mL / L, and the solvent is water; immersing the powder solid phase in the composite aqueous solution of zinc acetate and ethylene glycol, wherein the mass ratio of the powder solid phase immersed in the composite aqueous solution of zinc acetate and ethylene glycol is powder solid phase: composite aqueous solution of zinc acetate and ethylene glycol = 1:200; stirring for 5 min, then solid-liquid separation, calcining the solid phase at 400° C. for 30 min, air cooling to room temperature, and then immersing again in the composite aqueous solution of zinc acetate and ethylene glycol, stirring for 5 min, solid-liquid separation, and calcining the solid phase at 400° C. for 30 min; the above immersion, stirring, solid-liquid separation, calcining, and air cooling steps are a whole set, and a total of 6 sets are repeated to form zinc oxide on the surface of the powder to obtain a primary treated powder;
[0028] (3) preparing a dimethyl sulfoxide solution of isophorone diisocyanate; in the dimethyl sulfoxide solution of isophorone diisocyanate, the concentration of isophorone diisocyanate is 7 g / 100 mL, and the solvent is dimethyl sulfoxide; adding the once treated powder to the dimethyl sulfoxide and stirring for 10 min to form a dispersion, the mass ratio of the once treated powder to the dimethyl sulfoxide is once treated powder: dimethyl sulfoxide = 1:80; heating the dispersion to 70±3° C. in a water bath and then adding the isophorone diisocyanate to the dispersion under stirring; dimethyl sulfoxide solution of isophorone diisocyanate and dibutyltin dilaurate, and adding the dimethyl sulfoxide solution of isophorone diisocyanate and dibutyltin dilaurate to the dispersion in a mass ratio of dispersion: dimethyl sulfoxide solution of isophorone diisocyanate: dibutyltin dilaurate = 10:5:0.3; after the addition is completed, continue to stir at a constant temperature of 70±3°C for 6h, then air cool to room temperature, separate the solid and liquid, wash the solid phase with dimethyl sulfoxide twice, then wash with deionized water 3 times, and dry at 80°C for 3h to obtain a powder additive;
[0029] (4) The aluminum powder is passed through a 1000 mesh sieve, and the sieved powder is immersed in acetone for ultrasonic cleaning for 10 minutes to remove oil, and then the solid-liquid separation is performed, and the solid phase is dried at 60° C. for 15 minutes. The dried aluminum powder is added to anhydrous ethanol, and heated to 70±3° C. in a water bath in a nitrogen atmosphere for insulation, and then 3-aminopropyltriethoxysilane is added under stirring. The dried aluminum powder is added with anhydrous ethanol and 3-aminopropyltriethoxysilane in a ratio of aluminum powder: anhydrous ethanol: 3-aminopropyltriethoxysilane = 10 g: 100 mL: 20 mL; after the addition is completed, the mixture is stirred at a constant temperature of 70±3° C. for 3 hours in a nitrogen protective atmosphere, and the solid-liquid separation is performed after insulation, and the solid phase is dried at 60° C. for 2 hours to obtain modified aluminum powder;
[0030] (5) Weigh the raw material components, and the weight of each component is as follows: 100 parts of dehydrated polyether polyol (330N), 25 parts of toluene diisocyanate, 7 parts of 4,4'-diamino-3,3'-dichlorodiphenylmethane, 7 parts of the powder additive, 7 parts of the modified aluminum powder, 4 parts of titanium dioxide powder, 16 parts of calcium carbonate, 2 parts of BYK055 defoamer, and 3 parts of dibutyl phthalate; add the dehydrated polyether polyol to a reaction kettle, heat it to 80±2°C in a water bath, and then add toluene diisocyanate. After the addition is completed, continue to stir at a constant temperature of 80±2°C for 2 hours to obtain component A; mix 4,4'-diamino-3,3'-dichlorodiphenylmethane, the powder additive, the modified aluminum powder, titanium dioxide powder, calcium carbonate, defoamer, and dibutyl phthalate to obtain component B; mix component A and component B to obtain the waterproof exterior wall coating.
[0031] Example 3
[0032] A method for preparing a waterproof exterior wall coating for a building, the preparation steps comprising:
[0033] (1) In a reaction kettle, a glucose aqueous solution is prepared, wherein the glucose concentration in the glucose aqueous solution is 16 g / L, and the solvent is water; an sodium silicate aqueous solution is prepared, wherein the mass percentage of sodium silicate in the sodium silicate aqueous solution is 5%, and the solvent is water; an cerium nitrate aqueous solution is prepared, wherein the cerium nitrate concentration in the cerium nitrate aqueous solution is 15 g / L, and the solvent is water; the glucose aqueous solution is stirred, and then the sodium silicate aqueous solution is added to the glucose aqueous solution under stirring, and after the addition is completed, the mixture is stirred for 20 minutes, and then the cerium nitrate aqueous solution is added. , adding the aqueous solution of sodium silicate and the aqueous solution of cerium nitrate to the aqueous solution of glucose in a volume ratio of the aqueous solution of glucose: the aqueous solution of sodium silicate: the aqueous solution of cerium nitrate = 100:3:0.9; dropping ammonia water to adjust the pH of the solution to 8, wherein the mass percentage of the solute in the ammonia water is 25%; after the addition is completed, the reactor is sealed, heated to 180±5°C and kept warm for 20 hours, air-cooled to room temperature after keeping warm, the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed with deionized water for 3 times, dried at 80°C for 3 hours, and then calcined at 600°C for 5 hours to obtain a powder solid phase;
[0034] (2) preparing a composite aqueous solution of zinc acetate and ethylene glycol, wherein the concentration of zinc acetate is 35 g / L, the concentration of ethylene glycol is 8 mL / L, and the solvent is water; immersing the powder solid phase in the composite aqueous solution of zinc acetate and ethylene glycol, wherein the mass ratio of the powder solid phase immersed in the composite aqueous solution of zinc acetate and ethylene glycol is powder solid phase: composite aqueous solution of zinc acetate and ethylene glycol = 1:200; stirring for 5 min, then solid-liquid separation, calcining the solid phase at 400° C. for 30 min, air cooling to room temperature, and then immersing again in the composite aqueous solution of zinc acetate and ethylene glycol, stirring for 5 min, solid-liquid separation, and calcining the solid phase at 400° C. for 30 min; the above immersion, stirring, solid-liquid separation, calcining, and air cooling steps are a whole set, and a total of 6 sets are repeated to form zinc oxide on the surface of the powder to obtain a primary treated powder;
[0035] (3) preparing a dimethyl sulfoxide solution of isophorone diisocyanate; in the dimethyl sulfoxide solution of isophorone diisocyanate, the concentration of isophorone diisocyanate is 7 g / 100 mL, and the solvent is dimethyl sulfoxide; adding the once treated powder to the dimethyl sulfoxide and stirring for 10 min to form a dispersion, the mass ratio of the once treated powder to the dimethyl sulfoxide is once treated powder: dimethyl sulfoxide = 1:80; heating the dispersion to 70±3° C. in a water bath and then adding the isophorone diisocyanate to the dispersion under stirring; dimethyl sulfoxide solution of isophorone diisocyanate and dibutyltin dilaurate, and adding the dimethyl sulfoxide solution of isophorone diisocyanate and dibutyltin dilaurate to the dispersion in a mass ratio of dispersion: dimethyl sulfoxide solution of isophorone diisocyanate: dibutyltin dilaurate = 10:6:0.3; after the addition is completed, continue to stir at a constant temperature of 70±3°C for 6h, then air cool to room temperature, separate the solid and liquid, wash the solid phase with dimethyl sulfoxide twice, then wash with deionized water 3 times, and dry at 80°C for 3h to obtain a powder additive;
[0036] (4) The aluminum powder is passed through a 1000 mesh sieve, and the sieved powder is immersed in acetone for ultrasonic cleaning for 10 minutes to remove oil, and then the solid-liquid separation is performed, and the solid phase is dried at 60°C for 15 minutes. The dried aluminum powder is added to anhydrous ethanol, and heated to 70±3°C in a water bath in a nitrogen atmosphere. Then, 3-aminopropyltriethoxysilane is added under stirring. The dried aluminum powder is added with anhydrous ethanol and 3-aminopropyltriethoxysilane in a ratio of aluminum powder: anhydrous ethanol: 3-aminopropyltriethoxysilane = 10g: 100mL: 25mL; after the addition is completed, the mixture is stirred at a constant temperature of 70±3°C for 3 hours in a nitrogen protective atmosphere, and the solid-liquid separation is performed after insulation. The solid phase is dried at 60°C for 2 hours to obtain modified aluminum powder;
[0037] (5) Weigh the raw material components, and the weight of each component is as follows: 100 parts of dehydrated polyether polyol (330N), 25 parts of toluene diisocyanate, 7 parts of 4,4'-diamino-3,3'-dichlorodiphenylmethane, 8 parts of the powder additive, 8 parts of the modified aluminum powder, 4 parts of titanium dioxide powder, 17 parts of calcium carbonate, 3 parts of BYK055 defoamer, and 3 parts of dibutyl phthalate; add the dehydrated polyether polyol to a reaction kettle, heat it to 80±2°C in a water bath, and then add toluene diisocyanate. After the addition is completed, continue to stir at a constant temperature of 80±2°C for 2 hours to obtain component A; mix 4,4'-diamino-3,3'-dichlorodiphenylmethane, the powder additive, the modified aluminum powder, titanium dioxide powder, calcium carbonate, defoamer, and dibutyl phthalate to obtain component B; mix component A and component B to obtain the waterproof exterior wall coating.
[0038] Example 4
[0039] A method for preparing a waterproof exterior wall coating for a building, the preparation steps comprising:
[0040] (1) In a reaction kettle, an aqueous solution of glucose is prepared, wherein the concentration of glucose in the aqueous solution of glucose is 16 g / L, and the solvent is water; an aqueous solution of sodium silicate is prepared, wherein the mass percentage of sodium silicate in the aqueous solution of sodium silicate is 5%, and the solvent is water; an aqueous solution of cerium nitrate is prepared, wherein the concentration of cerium nitrate in the aqueous solution of cerium nitrate is 20 g / L, and the solvent is water; the aqueous solution of glucose is stirred, and then the aqueous solution of sodium silicate is added to the aqueous solution of glucose under stirring, and after the addition is completed, the mixture is stirred for 20 minutes, and then the aqueous solution of cerium nitrate is added. liquid, adding the aqueous solution of sodium silicate and the aqueous solution of cerium nitrate to the aqueous solution of glucose in a volume ratio of the aqueous solution of glucose: the aqueous solution of sodium silicate: the aqueous solution of cerium nitrate = 100:3:1; dropping ammonia water to adjust the pH of the solution to 8, wherein the mass percentage of the solute in the ammonia water is 25%; after the addition is completed, the reactor is sealed, heated to 180±5°C and kept warm for 20 hours, and then air-cooled to room temperature after keeping warm, the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed with deionized water for 3 times, dried at 80°C for 3 hours, and then calcined at 600°C for 5 hours to obtain a powder solid phase;
[0041] (2) preparing a composite aqueous solution of zinc acetate and ethylene glycol, wherein the concentration of zinc acetate is 40 g / L, the concentration of ethylene glycol is 9 mL / L, and the solvent is water; immersing the powder solid phase in the composite aqueous solution of zinc acetate and ethylene glycol, wherein the mass ratio of the powder solid phase immersed in the composite aqueous solution of zinc acetate and ethylene glycol is powder solid phase: composite aqueous solution of zinc acetate and ethylene glycol = 1:200; stirring for 5 min, then solid-liquid separation, calcining the solid phase at 400° C. for 30 min, air cooling to room temperature, and then immersing again in the composite aqueous solution of zinc acetate and ethylene glycol, stirring for 5 min, solid-liquid separation, and calcining the solid phase at 400° C. for 30 min; the above immersion, stirring, solid-liquid separation, calcining, and air cooling steps are a whole set, and a total of 6 sets are repeated to form zinc oxide on the surface of the powder to obtain a primary treated powder;
[0042] (3) preparing a dimethyl sulfoxide solution of isophorone diisocyanate; in the dimethyl sulfoxide solution of isophorone diisocyanate, the concentration of isophorone diisocyanate is 8 g / 100 mL, and the solvent is dimethyl sulfoxide; adding the once treated powder to the dimethyl sulfoxide and stirring for 10 min to form a dispersion, the mass ratio of the once treated powder to the dimethyl sulfoxide is once treated powder: dimethyl sulfoxide = 1:80; heating the dispersion to 70±3° C. in a water bath and then adding the isophorone diisocyanate to the dispersion under stirring; dimethyl sulfoxide solution of isophorone diisocyanate and dibutyltin dilaurate, and adding the dimethyl sulfoxide solution of isophorone diisocyanate and dibutyltin dilaurate to the dispersion in a mass ratio of dispersion: dimethyl sulfoxide solution of isophorone diisocyanate: dibutyltin dilaurate = 10:6:0.4; after the addition is completed, continue to stir at a constant temperature of 70±3°C for 6h, then air cool to room temperature, separate the solid and liquid, wash the solid phase with dimethyl sulfoxide twice, then wash with deionized water 3 times, and dry at 80°C for 3h to obtain a powder additive;
[0043] (4) The aluminum powder is passed through a 1000 mesh sieve, and the sieved powder is immersed in acetone for ultrasonic cleaning for 10 minutes to remove oil, and then the solid-liquid separation is performed, and the solid phase is dried at 60°C for 15 minutes. The dried aluminum powder is added to anhydrous ethanol, and heated to 70±3°C in a water bath in a nitrogen atmosphere. Then, 3-aminopropyltriethoxysilane is added under stirring. The dried aluminum powder is added with anhydrous ethanol and 3-aminopropyltriethoxysilane in a ratio of aluminum powder: anhydrous ethanol: 3-aminopropyltriethoxysilane = 10g: 100mL: 25mL; after the addition is completed, the mixture is stirred at a constant temperature of 70±3°C for 3 hours in a nitrogen protective atmosphere, and the solid-liquid separation is performed after insulation. The solid phase is dried at 60°C for 2 hours to obtain modified aluminum powder;
[0044] (5) Weighing the raw material components, the weight percentage of each component is as follows: 100 parts of dehydrated polyether polyol (330N), 30 parts of toluene diisocyanate, 8 parts of 4,4'-diamino-3,3'-dichlorodiphenylmethane, 10 parts of the powder additive, 10 parts of the modified aluminum powder, 6 parts of titanium dioxide powder, 18 parts of calcium carbonate, 3 parts of BYK055 defoamer, and 4 parts of dibutyl phthalate; adding the dehydrated polyether polyol into the reaction mixture; The kettle is heated to 80±2° C. in a water bath for heat preservation, and then toluene diisocyanate is added. After the addition is completed, stirring is continued at a constant temperature of 80±2° C. for 2 hours to obtain component A; 4,4'-diamino-3,3'-dichlorodiphenylmethane, the powder additive, the modified aluminum powder, titanium dioxide powder, calcium carbonate, defoaming agent, and dibutyl phthalate are mixed evenly to obtain component B; component A and component B are mixed evenly to obtain the waterproof exterior wall coating for building construction.
[0045] Comparative Example 1
[0046] A method for preparing an exterior wall coating as a comparison, the preparation steps comprising:
[0047] (1) In a reactor, a glucose aqueous solution is prepared, wherein the concentration of glucose in the glucose aqueous solution is 15 g / L, and the solvent is water; an aqueous solution of sodium silicate is prepared, wherein the mass percentage of sodium silicate in the sodium silicate aqueous solution is 4%, and the solvent is water; the glucose aqueous solution is stirred, and then the sodium silicate aqueous solution is added to the glucose aqueous solution under stirring, and stirred for 20 minutes after the addition is completed, and the volume ratio of the sodium silicate aqueous solution added to the glucose aqueous solution is the glucose aqueous solution: the sodium silicate aqueous solution = 100:2; ammonia water is added dropwise to adjust the solution pH to 8, and the mass percentage of the solute in the ammonia water is 25%; after the addition is completed, the reactor is sealed, heated to 180±5°C and kept warm for 20 hours, and then air-cooled to room temperature after the insulation, the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed with deionized water 3 times, dried at 80°C for 3 hours, and then calcined at 600°C for 5 hours to obtain the powder solid phase of this comparative example;
[0048] (2) preparing a composite aqueous solution of zinc acetate and ethylene glycol, wherein the concentration of zinc acetate is 35 g / L, the concentration of ethylene glycol is 7 mL / L, and the solvent is water; immersing the powder solid phase in the composite aqueous solution of zinc acetate and ethylene glycol, wherein the mass ratio of the powder solid phase immersed in the composite aqueous solution of zinc acetate and ethylene glycol is powder solid phase: composite aqueous solution of zinc acetate and ethylene glycol = 1:200; stirring for 5 min, then solid-liquid separation, calcining the solid phase at 400° C. for 30 min, air cooling to room temperature, and then immersing again in the composite aqueous solution of zinc acetate and ethylene glycol, stirring for 5 min, solid-liquid separation, and calcining the solid phase at 400° C. for 30 min; the above immersion, stirring, solid-liquid separation, calcining, and air cooling steps are a whole set, and a total of 6 sets are repeated to form zinc oxide on the surface of the powder to obtain a primary treated powder;
[0049] (3) preparing a dimethyl sulfoxide solution of isophorone diisocyanate; in the dimethyl sulfoxide solution of isophorone diisocyanate, the concentration of isophorone diisocyanate is 7 g / 100 mL, and the solvent is dimethyl sulfoxide; adding the once treated powder to the dimethyl sulfoxide and stirring for 10 min to form a dispersion, the mass ratio of the once treated powder to the dimethyl sulfoxide is once treated powder: dimethyl sulfoxide = 1:80; heating the dispersion to 70±3° C. in a water bath and then adding the isophorone diisocyanate to the dispersion under stirring; dimethyl sulfoxide solution of isophorone diisocyanate and dibutyltin dilaurate, and adding the dimethyl sulfoxide solution of isophorone diisocyanate and dibutyltin dilaurate to the dispersion in a mass ratio of dispersion: dimethyl sulfoxide solution of isophorone diisocyanate: dibutyltin dilaurate = 10:5:0.3; after the addition is completed, continue to stir at a constant temperature of 70±3°C for 6h, then air cool to room temperature, separate the solid and liquid, wash the solid phase with dimethyl sulfoxide twice, then wash with deionized water 3 times, and dry at 80°C for 3h to obtain a powder additive;
[0050] (4) The aluminum powder is passed through a 1000 mesh sieve, and the sieved powder is immersed in acetone for ultrasonic cleaning for 10 minutes to remove oil, and then the solid-liquid separation is performed, and the solid phase is dried at 60° C. for 15 minutes. The dried aluminum powder is added to anhydrous ethanol, and heated to 70±3° C. in a water bath in a nitrogen atmosphere for insulation, and then 3-aminopropyltriethoxysilane is added under stirring. The dried aluminum powder is added with anhydrous ethanol and 3-aminopropyltriethoxysilane in a ratio of aluminum powder: anhydrous ethanol: 3-aminopropyltriethoxysilane = 10 g: 100 mL: 20 mL; after the addition is completed, the mixture is stirred at a constant temperature of 70±3° C. for 3 hours in a nitrogen protective atmosphere, and the solid-liquid separation is performed after insulation, and the solid phase is dried at 60° C. for 2 hours to obtain modified aluminum powder;
[0051] (5) Weigh the raw material components, and the weight of each component is as follows: 100 parts of dehydrated polyether polyol (330N), 25 parts of toluene diisocyanate, 7 parts of 4,4'-diamino-3,3'-dichlorodiphenylmethane, 7 parts of the powder additive, 7 parts of the modified aluminum powder, 4 parts of titanium dioxide powder, 16 parts of calcium carbonate, 2 parts of BYK055 defoamer, and 3 parts of dibutyl phthalate; add the dehydrated polyether polyol to a reaction kettle, heat it to 80±2° C. in a water bath, and then add toluene diisocyanate. After the addition is completed, continue to stir at a constant temperature of 80±2° C. for 2 hours to obtain component A; mix 4,4'-diamino-3,3'-dichlorodiphenylmethane, the powder additive, the modified aluminum powder, titanium dioxide powder, calcium carbonate, defoamer, and dibutyl phthalate to obtain component B; mix component A and component B to obtain the exterior wall coating described in this comparative example.
[0052] Comparative Example 2
[0053] A method for preparing an exterior wall coating as a comparison, the preparation steps comprising:
[0054] (1) In a reaction kettle, an aqueous solution of glucose is prepared, wherein the concentration of glucose in the aqueous solution of glucose is 15 g / L, and the solvent is water; an aqueous solution of sodium silicate is prepared, wherein the mass percentage of sodium silicate in the aqueous solution of sodium silicate is 4%, and the solvent is water; an aqueous solution of cerium nitrate is prepared, wherein the concentration of cerium nitrate in the aqueous solution of cerium nitrate is 14 g / L, and the solvent is water; the aqueous solution of glucose is stirred, and then the aqueous solution of sodium silicate is added to the aqueous solution of glucose under stirring, and after the addition is completed, the mixture is stirred for 20 minutes, and then the aqueous solution of cerium nitrate is added to the aqueous solution of glucose; The volume ratio of the aqueous solution of sodium silicate and the aqueous solution of cerium nitrate is 100:2:0.9; the pH value of the solution is adjusted to 8 by dropping ammonia water, and the mass percentage of the solute in the ammonia water is 25%; after the addition is completed, the reactor is sealed, heated to 180±5°C and kept warm for 20 hours, and then air-cooled to room temperature after keeping warm, the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed with deionized water 3 times, dried at 80°C for 3 hours, and then calcined at 600°C for 5 hours to obtain a powder solid phase as the primary treated powder of this comparative example;
[0055] (2) preparing a dimethyl sulfoxide solution of isophorone diisocyanate; in the dimethyl sulfoxide solution of isophorone diisocyanate, the concentration of isophorone diisocyanate is 7 g / 100 mL, and the solvent is dimethyl sulfoxide; adding the once treated powder to the dimethyl sulfoxide and stirring for 10 min to form a dispersion, the mass ratio of the once treated powder to the dimethyl sulfoxide is once treated powder: dimethyl sulfoxide = 1:80; heating the dispersion to 70±3° C. in a water bath and then adding the isophorone diisocyanate to the dispersion under stirring; dimethyl sulfoxide solution of isophorone diisocyanate and dibutyltin dilaurate, and adding the dimethyl sulfoxide solution of isophorone diisocyanate and dibutyltin dilaurate to the dispersion in a mass ratio of dispersion: dimethyl sulfoxide solution of isophorone diisocyanate: dibutyltin dilaurate = 10:5:0.3; after the addition is completed, continue to stir at a constant temperature of 70±3°C for 6h, then air cool to room temperature, separate the solid and liquid, wash the solid phase with dimethyl sulfoxide twice, then wash with deionized water 3 times, and dry at 80°C for 3h to obtain a powder additive;
[0056] (3) The aluminum powder is passed through a 1000 mesh sieve, and the sieved powder is immersed in acetone for ultrasonic cleaning for 10 minutes to remove oil, and then the solid-liquid separation is carried out, and the solid phase is dried at 60°C for 15 minutes. The dried aluminum powder is added to anhydrous ethanol, and heated to 70±3°C in a water bath in a nitrogen atmosphere for insulation, and then 3-aminopropyltriethoxysilane is added under stirring. The dried aluminum powder is added with anhydrous ethanol and 3-aminopropyltriethoxysilane in a ratio of aluminum powder: anhydrous ethanol: 3-aminopropyltriethoxysilane = 10g: 100mL: 20mL; after the addition is completed, the mixture is stirred at a constant temperature of 70±3°C for 3 hours in a nitrogen protection atmosphere, and the solid-liquid separation is carried out after insulation, and the solid phase is dried at 60°C for 2 hours to obtain modified aluminum powder;
[0057] (4) Weigh the raw material components, and the weight of each component is as follows: 100 parts of dehydrated polyether polyol (330N), 25 parts of toluene diisocyanate, 7 parts of 4,4'-diamino-3,3'-dichlorodiphenylmethane, 7 parts of the powder additive, 7 parts of the modified aluminum powder, 4 parts of titanium dioxide powder, 16 parts of calcium carbonate, 2 parts of BYK055 defoamer, and 3 parts of dibutyl phthalate; add the dehydrated polyether polyol to a reaction kettle, heat it to 80±2° C. in a water bath, and then add toluene diisocyanate. After the addition is completed, continue to stir at a constant temperature of 80±2° C. for 2 hours to obtain component A; mix 4,4'-diamino-3,3'-dichlorodiphenylmethane, the powder additive, the modified aluminum powder, titanium dioxide powder, calcium carbonate, defoamer, and dibutyl phthalate to obtain component B; mix component A and component B to obtain the exterior wall coating described in this comparative example.
[0058] Comparative Example 3
[0059] A method for preparing an exterior wall coating as a comparison, the preparation steps comprising:
[0060] (1) In a reaction kettle, a glucose aqueous solution is prepared, wherein the glucose concentration in the glucose aqueous solution is 15 g / L, and the solvent is water; an sodium silicate aqueous solution is prepared, wherein the mass percentage of sodium silicate in the sodium silicate aqueous solution is 4%, and the solvent is water; an cerium nitrate aqueous solution is prepared, wherein the cerium nitrate concentration in the cerium nitrate aqueous solution is 14 g / L, and the solvent is water; the glucose aqueous solution is stirred, and then the sodium silicate aqueous solution is added to the glucose aqueous solution under stirring, and after the addition is completed, the sodium silicate aqueous solution is stirred for 20 minutes, and then the cerium nitrate aqueous solution is added. , adding the aqueous solution of sodium silicate and the aqueous solution of cerium nitrate to the aqueous solution of glucose in a volume ratio of the aqueous solution of glucose: the aqueous solution of sodium silicate: the aqueous solution of cerium nitrate = 100:2:0.9; dropping ammonia water to adjust the pH value of the solution to 8, wherein the mass percentage of the solute in the ammonia water is 25%; after the addition is completed, the reactor is sealed, heated to 180±5°C and kept warm for 20 hours, air-cooled to room temperature after keeping warm, the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed with deionized water for 3 times, dried at 80°C for 3 hours, and then calcined at 600°C for 5 hours to obtain a powder solid phase;
[0061] (2) preparing a composite aqueous solution of zinc acetate and ethylene glycol, wherein the concentration of zinc acetate is 35 g / L, the concentration of ethylene glycol is 7 mL / L, and the solvent is water; immersing the powder solid phase in the composite aqueous solution of zinc acetate and ethylene glycol, wherein the mass ratio of the powder solid phase immersed in the composite aqueous solution of zinc acetate and ethylene glycol is powder solid phase: composite aqueous solution of zinc acetate and ethylene glycol = 1:200; stirring for 5 min, then solid-liquid separation, calcining the solid phase at 400° C. for 30 min, air cooling to room temperature, and then immersing again in the composite aqueous solution of zinc acetate and ethylene glycol, stirring for 5 min, solid-liquid separation, and calcining the solid phase at 400° C. for 30 min; the above-mentioned immersion, stirring, solid-liquid separation, calcining, and air cooling steps are a whole group, and a total of 6 groups are repeated to form zinc oxide on the surface of the powder to obtain a once-treated powder as the powder additive of this comparative example;
[0062] (3) The aluminum powder is passed through a 1000 mesh sieve, and the sieved powder is immersed in acetone for ultrasonic cleaning for 10 minutes to remove oil, and then the solid-liquid separation is carried out, and the solid phase is dried at 60°C for 15 minutes. The dried aluminum powder is added to anhydrous ethanol, and heated to 70±3°C in a water bath in a nitrogen atmosphere for insulation, and then 3-aminopropyltriethoxysilane is added under stirring. The dried aluminum powder is added with anhydrous ethanol and 3-aminopropyltriethoxysilane in a ratio of aluminum powder: anhydrous ethanol: 3-aminopropyltriethoxysilane = 10g: 100mL: 20mL; after the addition is completed, the mixture is stirred at a constant temperature of 70±3°C for 3 hours in a nitrogen protection atmosphere, and the solid-liquid separation is carried out after insulation, and the solid phase is dried at 60°C for 2 hours to obtain modified aluminum powder;
[0063] (4) Weigh the raw material components, and the weight of each component is as follows: 100 parts of dehydrated polyether polyol (330N), 25 parts of toluene diisocyanate, 7 parts of 4,4'-diamino-3,3'-dichlorodiphenylmethane, 7 parts of the powder additive, 7 parts of the modified aluminum powder, 4 parts of titanium dioxide powder, 16 parts of calcium carbonate, 2 parts of BYK055 defoamer, and 3 parts of dibutyl phthalate; add the dehydrated polyether polyol to a reaction kettle, heat it to 80±2° C. in a water bath, and then add toluene diisocyanate. After the addition is completed, continue to stir at a constant temperature of 80±2° C. for 2 hours to obtain component A; mix 4,4'-diamino-3,3'-dichlorodiphenylmethane, the powder additive, the modified aluminum powder, titanium dioxide powder, calcium carbonate, defoamer, and dibutyl phthalate to obtain component B; mix component A and component B to obtain the exterior wall coating described in this comparative example.
[0064] Comparative Example 4
[0065] A method for preparing an exterior wall coating as a comparison, the preparation steps comprising:
[0066] (1) In a reaction kettle, a glucose aqueous solution is prepared, wherein the glucose concentration in the glucose aqueous solution is 15 g / L, and the solvent is water; an sodium silicate aqueous solution is prepared, wherein the mass percentage of sodium silicate in the sodium silicate aqueous solution is 4%, and the solvent is water; an cerium nitrate aqueous solution is prepared, wherein the cerium nitrate concentration in the cerium nitrate aqueous solution is 14 g / L, and the solvent is water; the glucose aqueous solution is stirred, and then the sodium silicate aqueous solution is added to the glucose aqueous solution under stirring, and after the addition is completed, the sodium silicate aqueous solution is stirred for 20 minutes, and then the cerium nitrate aqueous solution is added. , adding the aqueous solution of sodium silicate and the aqueous solution of cerium nitrate to the aqueous solution of glucose in a volume ratio of the aqueous solution of glucose: the aqueous solution of sodium silicate: the aqueous solution of cerium nitrate = 100:2:0.9; dropping ammonia water to adjust the pH value of the solution to 8, wherein the mass percentage of the solute in the ammonia water is 25%; after the addition is completed, the reactor is sealed, heated to 180±5°C and kept warm for 20 hours, air-cooled to room temperature after keeping warm, the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed with deionized water for 3 times, dried at 80°C for 3 hours, and then calcined at 600°C for 5 hours to obtain a powder solid phase;
[0067] (2) preparing a composite aqueous solution of zinc acetate and ethylene glycol, wherein the concentration of zinc acetate is 35 g / L, the concentration of ethylene glycol is 7 mL / L, and the solvent is water; immersing the powder solid phase in the composite aqueous solution of zinc acetate and ethylene glycol, wherein the mass ratio of the powder solid phase immersed in the composite aqueous solution of zinc acetate and ethylene glycol is powder solid phase: composite aqueous solution of zinc acetate and ethylene glycol = 1:200; stirring for 5 min, then solid-liquid separation, calcining the solid phase at 400° C. for 30 min, air cooling to room temperature, and then immersing again in the composite aqueous solution of zinc acetate and ethylene glycol, stirring for 5 min, solid-liquid separation, and calcining the solid phase at 400° C. for 30 min; the above immersion, stirring, solid-liquid separation, calcining, and air cooling steps are a whole set, and a total of 6 sets are repeated to form zinc oxide on the surface of the powder to obtain a primary treated powder;
[0068] (3) preparing a dimethyl sulfoxide solution of isophorone diisocyanate; in the dimethyl sulfoxide solution of isophorone diisocyanate, the concentration of isophorone diisocyanate is 7 g / 100 mL, and the solvent is dimethyl sulfoxide; adding the once treated powder to the dimethyl sulfoxide and stirring for 10 min to form a dispersion, the mass ratio of the once treated powder to the dimethyl sulfoxide is once treated powder: dimethyl sulfoxide = 1:80; heating the dispersion to 70±3° C. in a water bath and then adding the isophorone diisocyanate to the dispersion under stirring; dimethyl sulfoxide solution of isophorone diisocyanate and dibutyltin dilaurate, and adding the dimethyl sulfoxide solution of isophorone diisocyanate and dibutyltin dilaurate to the dispersion in a mass ratio of dispersion: dimethyl sulfoxide solution of isophorone diisocyanate: dibutyltin dilaurate = 10:5:0.3; after the addition is completed, continue to stir at a constant temperature of 70±3°C for 6h, then air cool to room temperature, separate the solid and liquid, wash the solid phase with dimethyl sulfoxide twice, then wash with deionized water 3 times, and dry at 80°C for 3h to obtain a powder additive;
[0069] (4) The aluminum powder was passed through a 1000-mesh sieve, and the sieved powder was immersed in acetone for ultrasonic cleaning for 10 minutes to remove oil, and then the solid-liquid separation was carried out, and the solid phase was dried at 60° C. for 15 minutes to obtain the aluminum powder of this comparative example;
[0070] (5) Weigh the raw material components, and the weight of each component is as follows: 100 parts of dehydrated polyether polyol (330N), 25 parts of toluene diisocyanate, 7 parts of 4,4'-diamino-3,3'-dichlorodiphenylmethane, 7 parts of the powder additive, 7 parts of the aluminum powder, 4 parts of titanium dioxide powder, 16 parts of calcium carbonate, 2 parts of BYK055 defoamer, and 3 parts of dibutyl phthalate; add the dehydrated polyether polyol to a reaction kettle, heat it to 80±2° C. in a water bath, and then add toluene diisocyanate. After the addition is completed, continue to stir at a constant temperature of 80±2° C. for 2 hours to obtain component A; mix 4,4'-diamino-3,3'-dichlorodiphenylmethane, the powder additive, the aluminum powder, the titanium dioxide powder, the calcium carbonate, the defoamer, and the dibutyl phthalate to obtain component B; mix component A and component B to obtain the exterior wall coating described in this comparative example.
[0071] Example 5
[0072] The exterior wall coatings prepared by the methods described in the above embodiments and comparative examples were painted into a paint film with a thickness of 2 mm, and then cured for 7 days at a temperature of 23±2°C and a humidity of 50%±10%, and then the water-impermeability and corrosion resistance of the paint film were tested. The water-impermeability was tested in accordance with the requirements of standard GB / T 16777-2008, and the corrosion resistance was tested in accordance with the requirements of standard GB / T1763-89, the corrosive medium was a sodium hydroxide aqueous solution with a mass percentage of 5%, the immersion time was 48 hours, and the temperature was 28°C. The test results are shown in Table 1.
[0073] As shown in Table 1, the paint film prepared by the method of the present invention has good waterproof effect and corrosion resistance, can play a good protective role on the exterior wall of the building, improve the quality of the exterior wall, and reduce maintenance costs. By comparing Example 2 of the present invention and each comparative example, it can be seen that the present invention can significantly improve the impermeability and corrosion resistance of the paint film by adding powder additives and modified aluminum powder, which is mainly due to: first, the cerium-doped nano silicon oxide powder is synthesized by a hydrothermal method, so that the additive powder has stronger chemical stability, and the specific surface area is significantly improved, and the bonding area between the additive powder and the paint film matrix is increased, so that the coating is more dense; subsequently, by coating the zinc oxide layer, on the one hand, it plays a role in activating the surface of the particles, providing conditions for subsequent modification, and on the other hand, the corrosion resistance of the particles after coating is significantly improved, preventing the corrosion of the silicon oxide particles by the corrosive liquid. Then, by grafting with isocyanate, the bonding strength between the particles and the paint film matrix is higher, the wettability of the two-phase interface is better, and it is beneficial to improve the dispersibility of the additive. In addition, by adding modified aluminum powder, the corrosion resistance of the paint film is further improved by utilizing the corrosion resistance of the aluminum powder itself. Aluminum powder has a certain shielding effect on moisture, and its impermeability is also improved after being added to the paint film.
[0074] Table 1
[0075]
[0076]
[0077] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A method for preparing a waterproof exterior wall coating for a building, It is characterized in that The preparation steps include: (1) preparing an aqueous solution of glucose, an aqueous solution of sodium silicate, and an aqueous solution of cerium nitrate in a reaction kettle; stirring the aqueous solution of glucose, and then adding the aqueous solution of sodium silicate to the aqueous solution of glucose under stirring, stirring for more than 20 minutes after the addition is completed, and then adding the aqueous solution of cerium nitrate, and adding ammonia water dropwise to adjust the pH value of the solution to 8; after the addition is completed, sealing the reaction kettle, heating to 180±5° C. and keeping the temperature for more than 20 hours, air cooling to room temperature after keeping the temperature, opening the reaction kettle, separating the solid and the liquid, washing the solid phase with deionized water for more than 3 times, drying at 80° C. for more than 3 hours, and then calcining at 600° C. for more than 5 hours to obtain a powder solid phase; (2) preparing a composite aqueous solution of zinc acetate and ethylene glycol, immersing the powder solid phase in the composite aqueous solution of zinc acetate and ethylene glycol, stirring for more than 5 minutes, then separating the solid and the liquid, calcining the solid phase at 400° C. for 30 to 40 minutes, air cooling to room temperature, and then immersing again in the composite aqueous solution of zinc acetate and ethylene glycol, stirring for more than 5 minutes, separating the solid and the liquid, and calcining the solid phase at 400° C. for 30 to 40 minutes; the above immersing, stirring, solid-liquid separation, calcining, and air cooling steps are a whole set, and are repeated for more than 6 sets in total, forming zinc oxide on the surface of the powder to obtain a primary treated powder; (3) preparing a dimethyl sulfoxide solution of isophorone diisocyanate; adding the once treated powder to dimethyl sulfoxide and stirring for more than 10 minutes to form a dispersion, heating the dispersion to 70±3° C. in a water bath and keeping it warm, then adding the dimethyl sulfoxide solution of isophorone diisocyanate and dibutyltin dilaurate to the dispersion under stirring, and continuing to stir at a constant temperature of 70±3° C. for more than 6 hours after the addition is completed, and then air cooling to room temperature, solid-liquid separation, washing the solid phase with dimethyl sulfoxide for more than two times, and then washing with deionized water for more than three times, and drying at 80° C. for more than 3 hours to obtain a powder additive; (4) passing aluminum powder through a 1000 mesh sieve, soaking the sieved powder in acetone for ultrasonic cleaning for more than 10 minutes, and then separating the solid and liquid, drying the solid phase at 60° C. for 15 to 20 minutes, adding the dried aluminum powder to anhydrous ethanol, heating to 70±3° C. in a water bath in a nitrogen atmosphere, and then adding 3-aminopropyltriethoxysilane under stirring. After the addition is completed, stirring at a constant temperature of 70±3° C. in a nitrogen protective atmosphere for more than 3 hours, separating the solid and liquid after insulation, and drying the solid phase at 60° C. for more than 2 hours to obtain modified aluminum powder; (5) Add the dehydrated polyether polyol to the reaction kettle, heat it to 80±2° C. in a water bath, and then add toluene diisocyanate. After the addition is completed, continue to stir at a constant temperature of 80±2° C. for 2 to 3 hours to obtain component A; mix 4,4'-diamino-3,3'-dichlorodiphenylmethane, the powder additive, the modified aluminum powder, titanium dioxide powder, calcium carbonate, defoaming agent, and dibutyl phthalate to obtain component B; mix component A and component B to obtain the waterproof building exterior wall coating.
2. A method for preparing a waterproof exterior wall coating for building construction according to claim 1, It is characterized in that In the step (1), in the aqueous solution of glucose, the concentration of glucose is 15-16 g / L, and the solvent is water; in the aqueous solution of sodium silicate, the mass percentage of sodium silicate is 4%-5%, and the solvent is water; in the aqueous solution of cerium nitrate, the concentration of cerium nitrate is 10-20 g / L, and the solvent is water; the volume ratio of the aqueous solution of sodium silicate and the aqueous solution of cerium nitrate added to the aqueous solution of glucose is glucose aqueous solution: sodium silicate aqueous solution: cerium nitrate aqueous solution = 100:2-3:0.8-1; the mass percentage of the solute in the ammonia water is 25%.
3. A method for preparing a waterproof exterior wall coating for building construction according to claim 1, It is characterized in that In the step (2), in the composite aqueous solution of zinc acetate and ethylene glycol, the concentration of zinc acetate is 30-40 g / L, the concentration of ethylene glycol is 6-9 mL / L, and the solvent is water; the mass ratio of the powder solid phase immersed in the composite aqueous solution of zinc acetate and ethylene glycol is powder solid phase: composite aqueous solution of zinc acetate and ethylene glycol = 1:
200.
4. A method for preparing a waterproof exterior wall coating for building construction according to claim 1, It is characterized in that In the step (3), the concentration of isophorone diisocyanate in the dimethyl sulfoxide solution of isophorone diisocyanate is 6-8 g / 100 mL, and the solvent is dimethyl sulfoxide; the mass ratio of the once-treated powder added to dimethyl sulfoxide is once-treated powder: dimethyl sulfoxide = 1:80; the mass ratio of the dimethyl sulfoxide solution of isophorone diisocyanate and dibutyltin dilaurate added to the dispersion is dispersion: dimethyl sulfoxide solution of isophorone diisocyanate: dibutyltin dilaurate = 10:5-6:0.2-0.
4.
5. A method for preparing a waterproof exterior wall coating for building construction according to claim 1, It is characterized in that In the step (4), the dried aluminum powder is added with anhydrous ethanol and 3-aminopropyltriethoxysilane in a ratio of aluminum powder: anhydrous ethanol: 3-aminopropyltriethoxysilane = 10 g: 100 mL: 20-25 mL.
6. A method for preparing a waterproof exterior wall coating for building construction according to claim 1, It is characterized in that In the step (5), the components are calculated by weight as follows: 100 parts of polyether polyol, 20-30 parts of toluene diisocyanate, 6-8 parts of 4,4'-diamino-3,3'-dichlorodiphenylmethane, 5-10 parts of the powder additive, 5-10 parts of the modified aluminum powder, 2-6 parts of titanium dioxide powder, 15-18 parts of calcium carbonate, 2-3 parts of defoaming agent, and 2-4 parts of dibutyl phthalate.
7. A method for preparing a waterproof exterior wall coating for building construction according to claim 6, It is characterized in that The defoamer is BYK055 defoamer.
